Willingness to pay in world heritage sites: a contingent valuation method at Red Fort Complex, New Delhi. Issue 2 (16th March 2021) - Danish, Mohammad
Willingness to pay-contingent valuation method (WTP-CVM) has emerged as one of the most reliable tools for pricing the entrance fee at the world heritage site. About 385 tourists' perceptions were recorded at the Red Fort Complex. A multiple regression analysis method was employed to establish the relationship between the dependent variable, WTP and other independent variables. Applications of the tools as 'multiple regression analysis' for the contingent valuation method assists in analysing the relationship between the dependent variable, WTP and other independent variables. Outcome of the analysis suggests a framework for the service enhancement and facilities augmentation at the site. This study has also suggested the three bands of WTP for the tourists; lowest, middle and highest. Keeping in consideration the different socio-economic strata of society, this 'one-time payment' would offer a flexible option to the tourists. This suggests a method to assess the economic sustainability of the UNESCO world heritage sites.